Peningkatan Ekonomi Kreatif Melalui Branding di Kawasan Pesisir Desa Mojosari Kecamatan Puger Kabupaten Jember - Majid, Nurkholish; Wardani, Nuruni Ika Kusuma; Hariyana, Nanik (Universitas Nusantara PGRI Kediri, 2022)
Mojosari Village, Puger District, Jember Regency has a Home Industry which is driven by Women Asociation of Welfare Guarantee (PKK) by processing seafood into crackers. However, the business is still underdeveloped in terms of: 1) Lack of variety and product diversification 2) Relatively simple of packaging, 3) Limitation of marketing distribution channels. The problem solution are by the way: 1) Increasing the value added of food by increase number of product variety and diversification, 2) increasing channel reach distribution of product marketing 3) Give knowledge transfer about business management. Implementation method by: focus group discussion, demonstration and practice. The results of activities such as: 1) Improving the quality and quantity of locally produced food-based food products 2) Improving skills about product diversification. 3) Increase marketing activities for raise sales.